Gate-controlled mid-infrared light bending with aperiodic graphene nanoribbons array. (11th March 2015) - Carrasco, Eduardo; Tamagnone, Michele; Mosig, Juan R; Low, Tony; Perruisseau-Carrier, Julien
Abstract: Graphene plasmonic nanostructures enable subwavelength confinement of electromagnetic energy from the mid-infrared down to the terahertz frequencies. By exploiting the spectrally varying light scattering phase at the vicinity of the resonant frequency of the plasmonic nanostructure, it is possible to control the angle of reflection of an incoming light beam. We demonstrate, through full-wave electromagnetic simulations based on Maxwell equations, the electrical control of the angle of reflection of a mid-infrared light beam by using an aperiodic array of graphene nanoribbons, whose widths are engineered to produce a spatially varying reflection phase profile that allows for the construction of a far-field collimated beam towards a predefined direction.